Sex-based differences on adverse left ventricular remodeling and clinical outcomes after an ST-segment elevation myocardial infarction in the PCI era. (3rd October 2022) - Alonso Tello, A; Sambola, A; Valente, F; Sao, A; Rello, P; Maymi, M; Barrabes, J; Otaegui, I; Garcia Del Blanco, B; Gavara, J; Marcos-Garces, V; Ferreira, I; et al.
Abstract: Background: There is conflicting evidence regarding sex-based differences in myocardial salvage and clinical outcome in patients after an ST-segment elevation myocardial infarction (STEMI) in the contemporary era of primary percutaneous coronary intervention (PCI) and optimal medical treatment. Adverse left ventricular remodelling (LVR) after a STEMI worsens outcomes, however, the influence of sex is not yet clear. Aim/Purpose: To analyze whether there are sex differences in clinical outcomes and adverse LVR in patients after a STEMI. Methods: Patients with STEMI who underwent primary PCI were included and a cardiac magnetic resonance (CMR) was performed during hospitalization (6.2±2.6 days) and after 6 months (6.1±1.8 months). LVR, myocardial salvage (MS), infarct size (IS), microvascular obstruction (MVO), and area at risk (AAR) were quantified. Adverse LVR was defined as a 15% increase in LV end-diastolic volume and a relative fall in LV ejection fraction of 3% at 6 months. The primary outcome was a composite of cardiovascular death, admission for heart failure, or ventricular arrhythmia. Results: A total of 1046 patients were included (mean age: 59.8±9 years; 16.6% women), and a second CMR was completed in 589 patients. Women were older (58.8±8 years vs 65.0±10 years, p<0.0001) and presented more cardiovascular risk factors (Table). The primary outcome occurred in 310 patients during follow-up of 75 months (range: 36–112 months) and was more frequent in women than in men (35.8% vs 22.3%, p<0.001). After adjusting for baseline differences (age, diabetes, hypertension, Killip class, and time to reperfusion), female sex was not an independent predictor of major adverse cardiac events (Fig. 1A & B). Although adverse LVR was a strong independent predictor for the primary outcome, no interaction was present between sex and LVR (women 6.4% vs men 8%, p=0.46) (Fig 1B), nor did we find significant differences between sex and other CMR derived variables such as MS, IS, MVO and AAR. Conclusions: After a STEMI, women present worse clinical outcomes than men. However, these differences are related to their clinical characteristics and higher incidence of cardiovascular risk factors, and not to a higher incidence of adverse left ventricular remodeling. Funding Acknowledgement: Type of funding sources: None.